Investigation of one-directional and bi-directional flows across staggered tube banks heat exchanger - Hasbullah, Nurjannah (2022)
One-directional and bi-directional flow conditions are different in terms of the direction of fluid flows. One-directional flow condition is when the fluid flows only in one direction. Meanwhile, bi-directional flow condition happens when the fluid flows in back and forth directions and this has been found in applications such as thermoacoustics. Thermoacoustics offer green technology for refrigeration and power cycles. The technology is appealing, but the lack of understanding on fluid dynamics and heat transfer behaviours of flow inside the system lead to the ambiguous use of equations from the well-known one-directional flow during the design stage and the impact of such estimation becomes evident as the flow in the real system becomes more complex. For this reason, experimental investigations that are supplemented by computational fluid dynamics modelling results are carried out with a focus on the heat exchanger. A staggered tube-banks heat exchanger was tested. A thermoacoustic’s standing wave rig with different type of flow inducers is used to create the one-directional and the bi-directional flows for the experiments. Results of velocity and temperature were recorded at the upstream and downstream locations of the staggered tube banks heat exchanger. The frequency of the bi-directional flow was set based on the resonance frequency of 14.2 Hz. Results indicate that temperature and velocity changes with respect to the change of flow amplitude are different between the one-directional and bi-directional flow conditions and the differences are in the range of 77 percent and 59.5 percent, respectively. A two-dimensional model of staggered tube banks heat exchanger is solved using a commercial software Ansys Fluent 16.0. The flow conditions were solved for the range of Reynolds between 270 and 1700 using SST k- turbulence models and the temperature contour, vorticity contour and the velocity vectors were discussed based on the results of the validated models. A similar trend of Nusselt number changes with the change of Reynolds number is seen between the experimental and numerical works of the one-directional flow and the bi-directional flow conditions, with errors of amplitude expected to be due to the limitations of experimental apparatus as well as the simplifications and assumptions made for the computational fluid dynamics works. Nevertheless, most recorded differences fell within the experimental uncertainty values of  2.8 to  5.8. The computational fluid dynamics models provided insight into the visualization of flow in area that could not be seen experimentally. Evidently, the bi-directional flow conditions are different compared to the one-directional flow condition by 65.85 percent at Reynolds number of 1300. Therefore, the use of the well-established one-directional flow equation on bi-directional flow conditions should be avoided should an accurate result is needed in the design stage of the future thermoacoustic energy systems.